"Riders on the storm": A co-teaching mentor model to increase student satisfaction and retention - Turkich, K.; Greive, Shane; Cozens, Paul (Queensland University of Technology, 2014)
This paper reports on a co-teaching mentor model focused on improving first year undergraduate retention rates through enhanced teaching practise. A lecturer responsible for first year units was partnered with a co-teaching mentor to offer guidance on how the content (urban and regional planning) could be delivered more effectively with an emphasis on student satisfaction and retention. We present a case study example where the findings demonstrate the effective transfer of teaching awareness and skills through this process. Five educational theories underpin the substantive changes made to the way classes were delivered. The applied relevance of these ideas can be demonstrated in the reflections from the participating lecturer of their teaching practices, and in the improved student evaluation and retention results.